2017
DOI: 10.1002/app.45697
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of amidoxime‐modified polyacrylonitrile nanofibrous adsorbents for the extraction of copper(II) and lead(II) ions and dye from aqueous media

Abstract: Amidoxime‐modified polyacrylonitrile nanofibrous films (AOPAN NFs) were prepared via an electrospinning technique. The traditional preparation methods for amidoximated polyacrylonitrile (AOPAN) solution were changed and improved. First, the PAN solution was modified by hydroxylamine hydrochloride to produce an AOPAN solution, and then, a small amount of inhibitor was added to the AOPAN solution for electrospinning. We found that the crosslinking of the AOPAN solution was inhibited by the addition of a small am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…These results indicated that the adsorption rate of Cu(II) on the surface-modified PAN fibers depended on the adsorbate concentration and the number of active sites of the adsorbent [24]. Previous studies have also revealed that the adsorption of Cu(II) on aminemodified PAN fibers followed the pseudo-second-order kinetic model [2,8,25]. .…”
Section: Adsorption Kineticsmentioning
confidence: 64%
See 1 more Smart Citation
“…These results indicated that the adsorption rate of Cu(II) on the surface-modified PAN fibers depended on the adsorbate concentration and the number of active sites of the adsorbent [24]. Previous studies have also revealed that the adsorption of Cu(II) on aminemodified PAN fibers followed the pseudo-second-order kinetic model [2,8,25]. .…”
Section: Adsorption Kineticsmentioning
confidence: 64%
“…The dependence of the adsorption of Cu(II) on surface-modified PAN fibers on the initial pH of the solution is presented in Figure 6. At low solution pH levels, the modified amine groups are protonated and the surface of the adsorbent is more positively charged, which is not favorable for the adsorption of metal cations [19,25]. The amount of Cu(II) ions adsorbed on the surface-modified PAN fibers increased significantly as the number of protonated amine groups decreased, owing to the increase in the solution pH [2].…”
Section: Effect Of Solution Ph On Cu(ii) Adsorptionmentioning
confidence: 99%
“…After chemical modification with TU, the FTIR spectra of polymer had showed significant changes, where the adsorption peak at 2,244 cm À1 had disappeared and new adsorption peaks at 1,614 cm À1 and 729 cm À1 had appeared. This can be attributed to the C ¼ N group and stretching vibration of C ¼ S bonds, respectively (Karthik et al 2017;Ren et al 2018). This had indicated that the chemical modification with TU was successful and thioamide groups were incorporated to the surface of polymer.…”
Section: Results and Discussion Characterization Of Synthesized Polymersmentioning
confidence: 96%
“…The adsorption peaks determined at 3,516 cm À1 could attribute to the O-H groups, while the characteristic peak found in 2,932 cm À1 are assigned to the stretching modes of C-H bonds (Buapeth et al 2019). The adsorption peaks of 2,244 cm À1 and 1,725 cm À1 represented the nitrile group (C≡N) and carbonyl group (C ¼ O), respectively (Yang et al 2017;Ren et al 2018). After chemical modification with TU, the FTIR spectra of polymer had showed significant changes, where the adsorption peak at 2,244 cm À1 had disappeared and new adsorption peaks at 1,614 cm À1 and 729 cm À1 had appeared.…”
Section: Results and Discussion Characterization Of Synthesized Polymersmentioning
confidence: 98%
“…However, the adsorption ability of PAN nanofibers for dyes removal from aqueous solutions still week due to its hydrophobic nature. Therefore, the surface modification of PAN nanofibers is an effective way to increase its hydrophilicity properties as well as the adsorption sites on the surface with keeping its morphology [154][155][156]. For example, Patel and Hota prepared PAN nanofibers and carboxylate-functionalized by alkaline hydrolysis using sodium hydroxide and sodium bicarbonate [157].…”
Section: Functionalized Epnfs As Adsorbent For Dyes Removalmentioning
confidence: 99%